The Effect of Regional Original Income, Balanced Funds and Regional Expenditures on Regional Financial Independence (Case Study in Central Java Province 2014-2018) - Dowes Ardinugroho; Albertus Maqnus Soesilo; Mulyanto Mulyanto (Budapest International Research and Critics University, 2021)
This study aims to test and provide empirical evidence regarding the effect of Regional Original Income (PAD), Balancing Funds, and Regional Expenditures on Regional Financial Independence in Central Java Province in 2014-2018. The number of observations in this study were 35 cities/districts in the province of Central Java. The data used is the visualization of APBD data, namely the realization of PAD, Balancing Funds, and Regency / City Regional Expenditures in Central Java Province from 2014-2018. The data is sourced from the Directorate General of Fiscal Balance, Ministry of Finance of Indonesia. Testing is done by analyzing panel data. The results of the panel data regression model on the Hausman Test show that the probability of a random cross-section in the Hausman test is 0.0000 <0.05, then H0 is accepted and the model selected in the Hausman test is Fixed Effect. Fixed Effect ResultsThe model shows that statistically the probability value (F-statistic) is 0.0000, meaning that the value is < from the alpha value of 0.05 and it can be said that the FEM regression model simultaneously independent variables (PAD, Balancing Fund, and Regional Expenditure) have a significant on the dependent variable (Regional Financial Independence). The R-squared value of 0.9874 indicates that the independent variables of PAD, Balancing Fund, and Regional Expenditure together are able to influence Independence by 98.74 percent and the remaining 1.26 percent is influenced by other variables not included in this research model